Knockdown of orexin type 2 receptor in the lateral pontomesencephalic tegmentum of rats increases REM sleep. Issue 6 (3rd January 2013) - Chen, Lichao; McKenna, James T.; Bolortuya, Yunren; Brown, Ritchie E.; McCarley, Robert W.
Abstract Dysfunction of the orexin/hypocretin neurotransmitter system causes the sleep disorder narcolepsy, characterized by intrusion of rapid eye movement (REM) sleep‐like events into normal wakefulness. The sites where orexins act to suppress REM sleep are incompletely understood. Previous studies suggested that the lateral pontomesencephalic tegmentum (lPMT) contains an important REM sleep inhibitory area, and proposed that orexins inhibit REM sleep via orexin type 2 receptors (OxR2) in this region. However, this hypothesis has heretofore not been tested. We thus performed bilateral injection of small interfering RNAs (siRNAs) targeting Ox2R into the lPMT on two consecutive days. This led to a approximately 30% increase of time spent in REM sleep in both the dark and light periods for the first 2 days after injection, with a return to baseline over the next two post‐injection days. This increase was mainly due to longer (> 120 s) REM episodes. Cataplexy‐like episodes were not observed. The percentage of time spent in wakefulness and non‐(N)REM sleep, as well as the power spectral profile of NREM and REM sleep, were unaffected. Control animals injected with scrambled siRNA had no sleep changes post‐injection. Quantification of the knockdown revealed that unilateral microinjection of siRNAs targeting OxR2 into the lPMT induced a approximately 40% reduction of OxR2 mRNA 2 days following the injections when compared with the contralateral side receiving control (scrambled) siRNA. Orexin type 1 receptor mRNA level was unaffected. Our results indicate that removal of OxR2 neurotransmission in the lPMT enhances REM sleep by increasing the duration of REM episodes.